Modeling technical and service efficiency. (February 2017) - Tsionas, Efthymios; Assaf, A. George; Gillen, David; Mattila, Anna S.
Highlights: We introduce a new model for measuring service efficiency and technical efficiency using Bayesian frontier methods. We illustrate our model with an application in the US airline industry. We discuss the determinants of bad outputs. We found high correlation between service inefficiency and consumer satisfaction. Abstract: Previous research on service failures, often measured by customer complaints, has not examined how organizations can measure or monitor their service efficiency. In this article, we introduce a new model that is suitable for measuring both service efficiency and technical efficiency when both bad outputs (i.e. service complaints) and good outputs (i.e. passenger trips and flights) are present. We develop our model with an output distance function, using Bayesian methods of inference organized around Markov chain Monte Carlo (MCMC). We illustrate our model with an application in the U.S. airline industry, an industry sector beset with service failures affecting both revenues and costs. We present the service inefficiency results of various US airlines and discuss the determinants of bad outputs in this industry. We also test whether our results are in line with market expectations by comparing the service efficiency estimates against the "American Customer Satisfaction Index" data.